Management of Plant-Parasitic Nematodes in Florida Soybean Production - Zane J. Grabau (EDIS)
This 8-page fact sheet written by Zane J. Grabau and published by the UF Department of Entomology and Nematology in January 2017 explains how to identify and manage a nematode issue in a soybean operation.http://edis.ifas.ufl.edu/ng018